Female sexual dysfunction: Definition, classification, and debates - Ching-Hui Chen; Yen-Chin Lin; Li-Hsuan Chiu; Yuan-Hsiang Chu; Fang-Fu Ruan; Wei-Min Liu; Peng-Hui Wang (Elsevier, 2013)
Sexual dysfunction refers to difficulties that occur during the sexual response cycle that prevent the individual from experiencing satisfaction from sexual activity. It is relatively difficult to estimate the prevalence of female sexual dysfunction (FSD), because the definition and diagnostic criteria are still controversial and under development. These difficulties reveal our insufficient understanding of the basis of FSD. This review was conducted in an effort to deal with this complicated clinical issue, by examining the most updated clinical criteria of FSD under the context of a redefined female sexual response model.